Crossfire ebook - Eason, Lynette (Extreme Measures, 2022)
FBI negotiator Julianna Jameson has never lost a hostage—until now. As the death toll rises and the killer's motive becomes clear, Julianna knows anyone she loves will get caught in the crossfire. It will take all her courage, and the help of Former Army Ranger Clay Fox, to bring this negotiation to an end.